Tandospirone activates neuroendocrine and ERK (MAP kinase) signaling pathways specifically through 5-HT1A receptor mechanisms in vivo - Sullivan, Nicole R.; Crane, James W.; Damjanoska, Katerina J.; Carrasco, Gonzalo A.; D’Souza, Deborah N.; Garcia, Francisca; Van de Kar, Louis D. (Naunyn-Schmiedeberg's archives of pharmacology, 2005)
Tandospirone, an azapirone, is a selective serotonin(1A) (5-HT(1A)) receptor agonist. The effects of tandospirone on plasma hormones and on mitogen-activated protein (MAP) kinase activity in the brain of male rats were studied. Tandospirone produced a time- and dose-dependent increase in plasma levels of oxytocin, adrenocorticotropin (ACTH), corticosterone, and prolactin. The minimal dose of tandospirone that led to a significant elevation of plasma oxytocin, ACTH, and prolactin levels was 1.0 mg/kg (s.c.), while the minimal dose for corticosterone release was 3.0 mg/kg (s.c.). The ED(50) of tandospirone was 1.3 mg/kg for oxytocin, 1.2 mg/kg for ACTH, 3.0 mg/kg for corticosterone, and 0.24 mg/kg for prolactin. Pretreatment with the specific 5-HT(1A) receptor antagonist WAY 100,635 (0.3 mg/kg, s.c.) completely blocked the effects of tandospirone on plasma levels of oxytocin, ACTH, and corticosterone but shifted the dose-response curve for prolactin to the right. Tandospirone injection (10 mg/kg, s.c.) stimulated the MAP kinase signaling cascade, specifically the phosphorylation of p42/44 extracellular signal-regulated kinase (ERK). Western blot analysis revealed a significant increase in phosphorylated ERK (p-ERK) levels in the hypothalamic paraventricular nucleus (PVN) as well as the dorsal raphe nucleus 5 min following tandospirone injection. These increases were blocked by pretreatment with WAY 100,635 (0.3 mg/kg). The results are the first evidence that systemic 5-HT(1A) receptor agonist administration produces a rapid increase in p-ERK levels in vivo, providing further insight into the signaling mechanisms of the 5-HT(1A) receptor.